Efektivitas E-Tilang bagi Pelaku Pelanggaran Lalu Lintas - Hanny Hanny; Asmin Patros (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2023)
Legal problems that often occur in Indonesian society are violations of the law in traffic. One of the efforts made by Indonesian law enforcement officers is the existence of a ticket. Traffic ticket cases are increasing from year to year, because nowadays we already have sophisticated technology, an E-Ticket was born which requires an information system and is supported by a software or website that can disseminate information to every law enforcement officer in real time. The Application of E-Tickets is very helpful for law enforcement officers in Indonesia. However, it can be said that E-Tickets has not been effective because there are still many Indonesian citizen who are technologically stumped. The application of E-Tilang is sourced or derived from electronic recordings or called E-TLE which has been mostly implemented in Indonesia.